Retracted: Detection of volatile organic compounds released by wood furniture based on a cataluminescence test system. (3rd August 2015) - Miao, Yanfeng; Deng, Fangming; Chen, Yulong; Guan, Huiyuan
Abstract: Wood furniture is an important source of indoor air pollution. To date, the detection of harmful substances in wood furniture has relied on the control of a single formaldehyde component, therefore the detection and evaluation of pollutants released by wood furniture are necessary. A novel method based on a cataluminescence (CTL) sensor system generated on the surface of nano‐3TiO2 –2BiVO4 was proposed for the simultaneous detection of pollutants released by wood furniture. Formaldehyde and benzene were selected as a model to investigate the CTL‐sensing properties of the sensor system. Field emission scanning electronic microscopy (FESEM), transmission electron microscopy (TEM) and X‐ray diffraction (XRD) were employed to characterize the as‐prepared samples. The results showed that the as‐prepared test system exhibited outstanding CTL properties such as stable intensity, a high signal‐to‐noise ratio, and short response and recovery times. In addition, the limit of detection for formaldehyde and benzene was below the standard permitted concentrations. Moreover, the sensor system showed outstanding selectivity for formaldehyde and benzene compared with eight other common volatile organic compounds (VOCs). The performance of the sensor system will enable furniture VOC limit emissions standards to be promulgated as soon as possible. Copyright © 2015 John Wiley & Sons, Ltd.